The complete mitochondrial genome of Dendrolimus kikuchii (Lepidoptera: Lasiocampidae) - Wu, Yu-Heng (Mitochondrial DNA B Resour, 2017)
As a serious forest pest on coniferous trees, Dendrolimus kikuchii has caused widespread concern in China. Here, its complete mitochondrial genome (mitogenome) has been sequenced with 15,382 bp in length. The mitogenome has a base composition of A (40.87%), T (37.83%), C (13.43%), and G (7.87%), and consists of 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, and an A + T-rich region. The phylogenetic relationships among the lasiocampid species were (Trabala vishnou+ ((Apatelopteryx phenax+ Euthrix laeta) + (Dendrolimus kikuchii+ (D. spectabilis+ (D. tabulaeformis + D. punctatus))))), which were supported by a posterior probability of 1.00 and a high bootstrap value of 100%.